Assembly Line Balancing and Sensitivity Analysis of a Single-Model Stochastic Sewing Line Using Arena Simulation Modelling - Hossain, Arif; Muneer, Khalid Ibn (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
Assembly line balancing is always a critical responsibility for manufacturers as it controls the efficiency and productivity of the assembly line. There are many techniques to solve line balancing problems, some of which are revealed in the literature review section, but computer-aided simulation modelling is prevalent among them. This study aims to analyze an assembly line balancing problem using a discrete event simulation software (Arena) for the optimal solution and sensitivity analysis of the solution. The empirical study was carried out at Arunima Sportswear Limited garment factory, and a garment style (kid’s pants) with 21 operations was taken into account. The computer model was verified by line supervisors and validated by a statistical hypothesis test (t-test). Then, using the Arena OptQuest tool, an optimal solution to the model is achieved. The average throughput of 904 pieces per day was achieved in the proposed model, which was 163 pieces higher than the existing model’s output. The line efficiency of the current model (75.76%) was also increased in the proposed model, which was 92.43%. Finally, a sensitivity analysis is performed by varying the values of some key factors (i.e., entities per arrival, process failure time, and operators’ absenteeism) to determine the level of uncertainty of the model.